Effects of heat exposure in the absence of hyperthermia on power output during repeated cycling sprints - Matsuura, R.; Arimitsu, T.; Yunoki, T.; Kimura, T.; Yamanaka, R.; Yano, T. (Biology of Sport, 2015)
The aim of this study was to investigate the effects of heat exposure in the absence of hyperthermia on power output during repeated cycling sprints. Seven males performed four 10-s cycling sprints interspersed by 30 s of active recovery on a cycle ergometer in hot-dry and thermoneutral environments. Changes in rectal temperature were similar under the two ambient conditions. The mean 2-s power output over the 1st-4th sprints was significantly lower under the hot-dry condition than under the thermoneutral condition. The amplitude of the electromyogram was lower under the hot-dry condition than under the thermoneutral condition during the early phase (0-3 s) of each cycling sprint. No significant difference was observed for blood lactate concentration between the two ambient conditions. Power output at the onset of a cycling sprint during repeated cycling sprints is decreased due to heat exposure in the absence of hyperthermia.